SOCIAL WORK-LED COUNSELING STRATEGIES WITH LINGUISTIC APPROACHES FOR SUICIDE PREVENTION IN MARGINALIZED COMMUNITIES - Yudistira, Satria (Esteem Journal of English Education Study Programme, 2025)
Counseling interventions coordinated by social work are essential for suicide prevention in underprivileged groups. Linguistic methodologies in counseling promote effective communication, improve comprehension, and foster trust between social workers and vulnerable children. This study examines optimal practices for applying counseling strategies that incorporate linguistic sensitivity among two underrepresented communities. The results indicate that this method effectively enhanced children's emotional regulation (80%), self-confidence (75%), and the formation of healthy interpersonal relationships (85%). Nonetheless, obstacles such as stigma associated with mental health care, parental opposition, and resource limitations persist as considerable impediments. Recommendations encompass training social workers in linguistically inclusive communication techniques, enhancing cross-sector policy support, and utilizing technology to broaden program outreach. This study emphasizes that incorporating language and cultural methodologies into social work counseling can effectively mitigate suicide risk in marginalized areas, ensuring communication is socially and culturally pertinent while promoting trust and engagement.